Pengembangan E-modul Multimedia Interaktif Berbasis Model Visual Auditory Kinesthetic untuk Meningkatkan Keterampilan Proses Sains dan Penguasaan Materi Fisika - Putri Rose Amanda Puri; Yusman Wiyatmo (Universitas Nurul Huda, 2024)
In physics learning, one of the skills needed is science process skills (KPS) because it can affect the level of mastery of physics material of students. However, the KPS and mastery of physics material of students are still low so that this research is carried out with the aim of producing physics interactive multimedia e-module based on the Visual Auditory Kinesthetic (VAK) model that are feasible, practical, and effective in improving KPS and mastery of physics material of students. R&D research method with 4D research design was used in this research. The feasibility of the media was assessed by one expert lecturer and one practitioner, the practicality of the media was obtained from students' responses to the media, and the effectiveness of the media was measured using the Pretest-Posttest Control Group design. This research was conducted on February 12 - March 15, 2024 at SMA N 1 Sanden involving class XI students as research samples. The data analysis techniques used include SBi, PA, N-Gain, Mann-Whitney test, and effect size. The results showed that the e-module was very feasible, practical, and effective in improving KPS with an N-gain of 0.47 (medium) and an effect size of 0.136 (medium) and mastery of material with an N-Gain of 0.31 (medium) and an effect size of 0.143 (very high).